The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1136/bmj.305.6866.1395
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and allergic disorders among children in united Germany: a descriptive comparison.

Abstract: Objectives-To compare the prevalence of asthma and allergic disorders among children in Munich, western Germany, and Leipzig, eastern Germany, where environmental exposure, particularly air concentrations of sulphur dioxide and particulate matter, and living conditions have differed over the past 45 years.Design-Prevalence surveys among schoolchildren aged 9-11 years in Leipzig and Munich. Self completion of written questionnaire by the children's parents and lung function measurements.Subjects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
171
3
13

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(214 citation statements)
references
References 26 publications
27
171
3
13
Order By: Relevance
“…Several studies have reported no association; some of these studies had small numbers of asthmatic children (Ellegard, 1996;Noorhassim et al, 1995). Several studies, including early papers by von Mutius and others comparing East and West Germany (Nowak et al, 1996;Von Mutius et al, 1992) and the main ISAAC papers (Mallol et al, 2000;ISAAC, Steering Committee, 1998), have reported lower asthma prevalence in areas with higher outdoor air pollution, indicating a counterintuitive protective effect of particle exposure, that is probably due to confounding. These papers, mainly of ecologic design, have influenced the scientific communities' ways of thinking about air pollution in such a way that this exposure is often not considered an important risk factor for asthma.…”
Section: Biomass-smoke Exposurementioning
confidence: 99%
“…Several studies have reported no association; some of these studies had small numbers of asthmatic children (Ellegard, 1996;Noorhassim et al, 1995). Several studies, including early papers by von Mutius and others comparing East and West Germany (Nowak et al, 1996;Von Mutius et al, 1992) and the main ISAAC papers (Mallol et al, 2000;ISAAC, Steering Committee, 1998), have reported lower asthma prevalence in areas with higher outdoor air pollution, indicating a counterintuitive protective effect of particle exposure, that is probably due to confounding. These papers, mainly of ecologic design, have influenced the scientific communities' ways of thinking about air pollution in such a way that this exposure is often not considered an important risk factor for asthma.…”
Section: Biomass-smoke Exposurementioning
confidence: 99%
“…Several surveys in children and adults have shown significantly lower prevalences of asthma and allergic diseases in eastern Europe than in western countries (113)(114)(115). In the former East Germany tremendous changes towards western lifestyle have occurred as unification and have lead to a similar rate of atopy (116).…”
Section: Role Of Infections In the Prevention Of Allergymentioning
confidence: 99%
“…Von Mutius et al (16) compared the prevalence of asthma in schoolchildren from the cities of Munich and Leipzig in the reunified Germany. The level of pollution was far higher in Leipzig.…”
Section: Epidemiological Backgroundmentioning
confidence: 99%
“…In addition, the prevalence of atopy has risen steadily in East Germany since lifestyle and environment have become more westernized. This suggests that the increase in the prevalence of allergic disease is probably due to factors associated with a western lifestyle (16).…”
Section: Epidemiological Backgroundmentioning
confidence: 99%